Remote Monitoring in Patients with Pacemakers and Implantable Cardioverter-Defibrillators: New Perspectives for Complex Therapeutic Management - Müller, Axel; Helms, Thomas M.; Wildau, Hans-Jürgen; Schwab, Jörg Otto; Zugck, Christian (IntechOpen, 2011)
None